Benzo[a]pyrene Emerging Micropollutant Oxidation under the Action of Fenton Reactants in Real Surface Water: Process Optimization and Application (2019)
This work evaluates the efficiency of the Fenton reaction on oxidizing 3 µg/L benzo[a]pyrene (BaP), used as a polycyclic aromatic hydrocarbon model compound due to the detrimental effects ascribed to its presence in aqueous media. For optimizing the variables affecting the oxidation capacity of the system, response surface methodology was conducted using a face-centered central composite experimental design. H2O2 and Fe(II) ion contents were studied in the range from 5 to 15 mg/L and from 0.21 to 0.63 mg/L, respectively. A poor BaP oxidation was observed in natural water since only ∼25% of BaP removal was obtained for an oxidant level of 10.50 mg/L and a catalyst concentration of 0.44 mg/L, after 90 min of treatment. Under these operating conditions, <10% of organic matter mineralization, in terms of total organic carbon, was achieved. However, by using a simpler aqueous matrix, 76.93% of BaP elimination was found; therefore, the efficiency of the process was increased by three-fold. This fact evidences the importance of performing investigations on advanced oxidation process application using real matrices; otherwise, erroneous conclusions about the efficiency of the system might be obtained. Additionally, the current work allows understanding the individual effects and relationships of the considered factors in the removal of the pollutant of interest at ultra-trace levels in a natural aqueous matrix. Keywords: Advanced oxidation processwater treatmentpolycyclic aromatic hydrocarbonresponse surface methodologyreal aqueous matrix